Usefulness and Usability of a Web-Based System for Disseminating Maize Production Knowledge in the Manyara Region, Tanzania - Victor Ngessa; Kisangiri Michael; Kelvin Mtei; Mawazo Magesa (Journal of Agricultural Extension)
This study designed and evaluated the usefulness and usability of a web-based system for disseminating maize production knowledge to farmers in Tanzania’s Manyara region. The system covered all stages of maize production, from farm preparation to harvesting and storage, and provided knowledge in multimedia formats with interactive features. Eighty-one smallholder maize farmers from Hanang, Mbulu, and Babati districts evaluated the system's usefulness and usability (satisfaction) via questionnaires, while an additional 10 respondents assessed its usability in terms of effectiveness and efficiency. Researchers observed respondents using the system to assess its effectiveness and efficiency. Data were analysed both quantitatively and qualitatively. Results showed that most smallholders found the system’s content and features useful ( =4.5). With an average System Usability Scale score of 87.5 and all users successfully completing tasks, the system proved easy to use. The study highlights the need for designing useful and user-friendly web-based systems, like the one under study, to help smallholders in developing countries access crop production knowledge, enhancing their productivity and decision-making capabilities.